Contraceptive use among HIV-positive and negative women: implication to end unintended pregnancy - Amanual Getnet Mersha; Daniel Asfaw Erku; Sewunet Admasu Belachew; Asnakew Achaw Ayele; Begashaw Melaku Gebresillassie; Tadesse Melaku Abegaz (Contraception and Reproductive Medicine, 2019)
Abstract Background With the advancement of antiretroviral therapy and improved life expectancy, women living with HIV/AIDS are enjoying a better sexual life. Yet, the consistent utilization of contraceptive in such patients is highly recommended. There is paucity of data regarding contraceptive use among HIV-positive and negative women in Ethiopia. The present study aimed at examining the use of contraceptives among HIV-positive and HIV-negative women in Ethiopia. Methods A comparative cross-sectional study was conducted among HIV-positive and HIV-negative women attending family planning Clinic of Gondar university referral hospital between January 2016 and August 2017. Descriptive statistics were used to present categorical data and Pearson’s chi-square test was done to examine differences in the utilization of contraceptives between HIV-positive and HIV-negative women. Kaplan Meier test was also carried out to determine the incidence of unintended pregnancy. A p-value of 0.05 was deemed significant with corresponding 95% confidence intervals. Results A total of 894 participants consisting of 314 HIV-positive and 580 HIV-negative women were included in the study. The rate of previous unintended pregnancy was 280 (31.3%) in HIV-negative women and 115 (12.9%) in HIV-infected women. Women who routinely utilized contraceptives were more likely to avoid unintended pregnancy [log rank: 2.89, p < 0.05]. Unlike HIV-negative women (2.9%), HIV-positive (28.4%) women reported a higher rate of intrauterine device use. Male condom was used more commonly in HIV-infected women (26.7%) as compared to HIV negative (3.9%) women (p-value < 0.05). Conclusions Intrauterine contraceptive device was reported to be the most commonly used contraceptive method in HIV patients. Further, unintended pregnancy was relatively common in women with low contraceptive practice. The use of dual contraceptives should be advocated for HIV-positive women so as to protect unintended pregnancy and curtail the transmission of HIV.